A Model for Optimizing Operating Profit Considering the Suboptimal Distribution of Production Resources with Emphasis on Accrual Items - Torabi Moghaddam, Arezo; Karbassi Yazdi, Hossein; Basirat, Behrouz (Management Strategies and Engineering Sciences, 2024)
Accrual items, as accounting entries recorded by company accountants before actual realization, are considered a type of accounting registration that can have a positive effect on profits, increase transparency, and ultimately attract the attention and trust of stakeholders. Therefore, significant emphasis has been placed on this subject in the accounting literature. However, the reality is that there is no model in the research literature that uses operations research methods to examine the effect of accrual items on operating profit. Given the benefits and usefulness of accrual items, this gap in research can be considered a research gap. The present study, addressing this gap, proposes a model for optimizing operating profit considering the suboptimal distribution of production resources and based on accrual items. The proposed model indicates that accrual items have a positive effect on operating profit, and as their ratio to cash items increases, this effect becomes more pronounced. Specifically, it is expected that accrual sales will have an effect of approximately 18%, and accrual expenses will have an effect of approximately 20% on operating profit.